Porous Biochar Supported Transition Metal Phosphide Catalysts for Hydrocracking of Palm Oil to Bio-Jet Fuel - Napat Kaewtrakulchai; Araya Smuthkochorn; Kanit Manatura; Gasidit Panomsuwan; Masayoshi Fuji; Apiluck Eiad-Ua (My University, 2022)
The upgrading of plant-based oils to liquid transportation fuels through the hydrotreating process has become the most attractive and promising technical pathway for producing biofuels. This work produced bio-jet fuel (C9-C14 hydrocarbons) from palm olein oil through hydrocracking over varied metal phosphide supported on porous biochar catalysts. Relative metal phosphide catalysts were investigated for the highest performance for bio-jet fuel production. The palm oil's fiber-derived porous biochar (PFC) revealed its high potential as a catalyst supporter. A series of PFC-supported cobalt, nickel, iron, and molybdenum metal phosphides (Co-P/PFC, Ni-P/PFC, Fe-P/PFC, and Mo-P/PFC) catalysts with a metal-loading content of 10 wt.% were synthesized by wet-impregnation and a reduction process. The performance of the prepared catalysts was tested for palm oil hydrocracking in a trickle-bed continuous flow reactor under fixed conditions; a reaction temperature of 420 °C, LHSV of 1 h-1, and H2 pressure of 50 bar was found. The Fe-P/PFC catalyst represented the highest hydrocracking performance based on 100% conversion with 94.6% bio-jet selectivity due to its higher active phase dispersion along with high acidity, which is higher than other synthesized catalysts. Moreover, the Fe-P/PFC catalyst was found to be the most selective to C9 (35.4%) and C10 (37.6%) hydrocarbons.
Keywords: Phosphide; Jet fuel; Residual oil; Space velocity; Catalysis and Hydrodesulfurization Studies